Influência do cátion manganês-II como agente abiótico no metabolismo secundário de fungos extremófilos do gênero Talaromyces - Alves, Mauricio Augusto Pinto Moreno da Silva (Universidade Federal de São Carlos, 2025)
This study investigated the impact of the manganese-(II) cation as an abiotic inducer in modulating the secondary metabolism of extremophilic fungi of the genus Talaromyces, with a focus on the production of bioactive compounds with antioxidant potential. Three experimental models were conducted using the species Talaromyces sp., Talaromyces fuscoviridis, and Talaromyces aureolinus, cultivated in modified media containing different concentrations of Mn²⁺, aiming to activate latent biosynthetic pathways and promote the generation of novel or poorly explored secondary metabolites. In Chapter 1, the effect of increasing manganese concentrations (0 to 1000 mM) on the metabolic profile of Talaromyces sp. was evaluated, with emphasis on significant alterations in polyketides involved in the mixed pathway of meroterpenoid biosynthesis. Seven compounds were isolated and characterized by NMR and HRMS, including phenols and hydroxybenzoic acids. Multivariate analyses (PCA and dendrogram) revealed that intermediate concentrations (125 and 250 mM) induced distinct changes in the chemical profile, suggesting disruption in the biosynthesis of specific metabolites. In Chapter 2, the extracts were subjected to antioxidant screening using an adapted DPPH-UPLC assay. The addition of Mn²⁺ enhanced the antioxidant activity of specific fractions, correlating oxidative stress with the increased production of phenolic and aromatic compounds. GC-MS analysis allowed the annotation of substances absent in the control extracts. In Chapter 3, the study focused on the fungus Talaromyces fuscoviridis, isolated from soil contaminated by copper mine tailings. The production of polyene steroids was stimulated by cultivation in rice supplemented with Mn²⁺, resulting in the isolation of two major compounds: Ergosta-3(4),7,14,22-tetraene (1a), unprecedented in the literature, and Ergosta-5,7,14,22-tetraen-3β-ol (2a), with structures confirmed by 1D/2D NMR, HRMS, and X-ray diffraction. Both exhibited antioxidant activity greater than 80% compared to β-carotene at low concentrations. PCA analysis showed clear separation between samples with and without Mn²⁺, confirming the inducing role of the cation in steroidal biosynthesis. Finally, in Chapter 4, three lactone depsidones were isolated and quantified from Talaromyces aureolinus grown in Czapek medium and rice supplemented with manganese: compound 1 (11-hydroxy-3-(1-hydroxy-3-methylbutyl)-4-methoxy-9-methyl-5H,7H-dibenzo[b,g][1,5]dioxocin-5-one), compound 2 (7-hydroxy-4,11-dimethoxy-3-vinyl-5H,7H-dibenzo[b,g][1,5]dioxocin-5-one), and compound 3 (1,6-dihydroxy-8-methyl-11H-dibenzo[b,e][1,4]dioxepin-11-one). Quantification by UPLC-MS indicated that Mn²⁺ favored the production of all three isolated compounds, suggesting a selective effect on the lactone biosynthetic pathway. The integration of spectroscopic data and molecular networking (GNPS) revealed alterations in the global chemical profile, with distinct clustering between treatments with and without Mn²⁺. The results demonstrate that manganese acts as an effective modulator of metabolic expression in extremophilic fungi, favoring the production of metabolites with biotechnological potential. This research contributes to the understanding of the adaptive response of these organisms to metal-induced stress and provides a basis for the rational exploration of microbial biodiversity as a source of novel bioactive compounds.
Influence of the cation manganese-II as an abiotic agent on the secondary metabolism of extremophilic fungi of the genus Talaromyces
Keywords: Fungos extremófilos; Talaromyces sp; Talaromyces fuscoviridis; Talaromyces aureolinus; Compostos bioativos; Extremophilic fungi; Bioactive compounds; CIENCIAS EXATAS E DA TERRA::QUIMICA